Relationship between interest rate, composite index and finance index / Nik Nuur Ellina Nik Mohamed - Nik Mohamed, Nik Nuur Ellina (2000)
The main purpose of this study is to determine whether there exists any relationship between Kuala Lumpur Stock Exchange and interest rate as well as relationship between Finance Index and interest rate. Literature review of related studies are discussed in Chapter 2. Subsequently, Chapter 3 continues with a brief exposure on Malaysia's Capital Market, Stock Index and Interest Rate. A description of Research and Methodology are discussed in Chapter 4. Data are collected on monthly basis for a period from January 1997 to December 1999. There are thirty-six observations of each variable. The findings have been tested with a Simple-Regression and Correlation Analysis by using SPSS Software. From the analysis carried out, it can be concluded that there is a relationship between interest rate and KLCI and between interest rate and Finance Index. The study also indicates that the relationship is negative for both KLCI and Finance Index.